Multicultural Literature of the USA - Tulaboeva Gulorom Tulaboevna (Genius Journals, 2022)
The generalization of all theories about character defining, giving information about the basic base concepts and some classifications of semiology or semiology, recognizing the word as either a kind of sign and highlighting its semiotic significance in linguistics. The XX century was marked by several events of worldwide influence, namely – the World War I, the Great Depression and the World War II. These events constituted the topics which also influenced publishing in American literature. A significant part of the American multi-ethnic literature is formed by Chinese American authors describing their experience in the United States throughout the generations. The Chinese American literature originated in the 1850’s when the first Chinese immigrants reached America and wanted to share their experience with other people. The early Chinese works depict American history from a point of view of immigrants to the United States, using their Chinese background for comparison with the American reality
Keywords: Multi-ethnic literature; immigrant’s experience; fiction; poetry